2009
DOI: 10.1271/bbb.80539
|View full text |Cite
|
Sign up to set email alerts
|

Hypocholesterolemic Effect of Peanut Skin and Its Fractions: A Case Record of Rats Fed on a High-Cholesterol Diet

Abstract: Peanut skin (PS) is characterized by almost exclusively consisting of polyphenols and fiber. We fractionated PS into a water-soluble fraction (WSF) and waterinsoluble fraction (WIF), and further fractionated WSF into a soluble dietary fiber fraction (DF) and dietary fiber-free, water-soluble fraction (DFF-WSF). Male Sprague-Dawley rats were fed on high-cholesterol diets supplemented with PS and its fractions. PS, WSF, and DFF-WSF decreased the serum lipid and cholesterol levels and increased those in feces. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 10 publications
1
25
0
Order By: Relevance
“…PSE was prepared as described previously. 12) In brief, peanut skins were boiled in purified water, and the residue was separated from the supernatant and boiled again in purified water. This was done 5 times, and then all the supernatants were concentrated in vacuo to produce PSE.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PSE was prepared as described previously. 12) In brief, peanut skins were boiled in purified water, and the residue was separated from the supernatant and boiled again in purified water. This was done 5 times, and then all the supernatants were concentrated in vacuo to produce PSE.…”
Section: Methodsmentioning
confidence: 99%
“…11) Our group also found a hypocholesterolemic effect of PSE in rats fed a high-cholesterol diet. 12) Recent studies have indicated that oral injection of procyanidin A1 lowers serum IgE and IgG1 levels in mice, suggesting that it has an anti-allergic effect in vivo, 13) but no effect of peanut-skin procyanidins has been reported at the cellular level.…”
mentioning
confidence: 99%
“…In recent studies, rats were used to investigate the hypocholesterolemic effects of soluble and insoluble fibre [1], plant proteins [2,3], chitosan [4], algae Chlorella [5], α-ketoglutarate [6], aluminosilicates [7], amidated pectin [8], and interesterified oils [9]. Compared to guinea pigs [10] and hamsters [11], rats are less susceptible to hypercholesterolaemia induction by dietary cholesterol, presumably because the high activity of hepatic cholesterol 7α-hydroxylase allows these rodents to convert excess dietary cholesterol to bile acids [10].…”
Section: Introductionmentioning
confidence: 99%
“…Insoluble carob fiber rich in polyphenols lowered total and LDL cholesterol levels in hypercholesterolemic subjects (8). The skin of peanuts and its fraction, which contains polyphenol, decreased serum lipid and cholesterol levels by inhibiting cholesterol absorption in the intestine (12).…”
mentioning
confidence: 99%